Konstitusi Sebagai Dasar Negara: Analisis Fungsi, Kedudukan, dan Perubahannya - Destiar Dimas Adhajanua; Rianita Muttofi’ah; Tazkia Yusnidar Harahap; Zaenul Slam (LP3M STITNU AL HIKMAH MOJOKERTO, 2026)
The constitution constitutes the supreme legal foundation within a state’s legal framework and function as the principal guideline for the governance and administration of public affairs. Beyond regulating the organization of state institutions and the allocation of governmental powers, it also safeguards human rights and reinforces the principles of constitutionalism, democracy, and the rule of law. This study seeks to analyze the concept and characteristic of constitution its functions as the legal basis and guiding framework of the state, its position within the hierarchy of legislation, its role in protecting human rights, the procedures for constitutional amendment, and the development of constitutional changes in Indonesia along with their implications for the governmental system. The research adopts a literature review approach through the examination of various scholarly sources, including books, national journals, and international journal publications. The findings reveal that the constitution serves a vital function in restricting governmental authority, ensuring the protection of citizens' rights, and fostering a democratic and accountable governance system. Furthermore, the amendments to the 1945 Constitution have brought significant transformations to Indonesia’s constitutional order by strengthening checks and balances among state institutions, creating new constitutional bodies, enhancing human rights protection, and broadening regional autonomy. Consequently, the constitution remains an essential instrument for promoting the rule of law, democratic governance, and social justice for all Indonesian citizens.